Democratic Control of the Military in Postcommunist Europe
XII, 273 p.
Keywords: This major comparative study examines the challenges that the countries of postcommunist Central and Eastern Europe have faced in securing democratic control of their armed forces and establishing civilian control of defence policy. This book explores how the interaction of the common challenges of postcommunism and the diverse circumstances of individual countries shape civil-military relations in this changing region. Detailed country case studies, written by leading experts, compare the experiences of the Central European states (such as Poland and Romania), the Baltic republics, the former Yugoslavia republics, Russia and Ukraine.